OPTIMALISASI PENERAPAN PROTOKOL KESEHATAN PADA PEKERJA DI KOTA SURABAYA - Dani Nasirul Haqi; Shintia Yunita Arini (Universitas Airlangga, 2021)
COVID-19 is a disease that caused by SARS-CoV-2 and the transmission of COVID-19 occurs when the droplets from an infected person enter the respiratory tract. COVID-19 cases in Surabaya kept increasing day by day, hence the optimum implementation of health protocols needed to be done, including in the group of workers. Workers were a group at high risk of contracting COVID-19, because there was a high possibility of workers making contact with other people in the workplace. The aim of this community service was to optimize the health protocol implementation to the workers in Surabaya. The methods used in this community service were counseling and online discussion. This activity was in collaboration with Surabaya Manpower Department and RRI Radio. The counselling was given by the lecturers of Airlangga University Public Health Faculty to the workers. The topic was about hazard identification, risk assessment and determining control (HIRADC) related to the optimization the health protocol implementation in the workplace, especially about the COVID-19 controls that could be applied by the workers in the workplace. The online discussion was led also by the lecturers of Airlangga University Public Health Faculty, discussing about questions and obstacles related to the implementation of health protocols in the workplace.abstrakCOVID-19 merupakan penyakit yang disebabkan oleh virus SARS-CoV-2 dan penularannya terjadi apabila droplets dari orang yang terinfeksi masuk ke dalam saluran pernapasan. Kasus COVID-19 di Kota Surabaya terus mengalami peningkatan setiap harinya, sehingga penerapan protokol kesehatan secara optimal perlu dilakukan di Kota Surabaya, salah satunya adalah pada kelompok pekerja. Hal ini karena kelompok pekerja merupakan kelompok berisiko tinggi tertular COVID-19 karena adanya kemungkinan yang tinggi pekerja melakukan kontak dengan orang lain ketika berada di tempat kerja. Tujuan dari pengabdian masyarakat ini adalah mengoptimalisasi penerapan protokol kesehatan pada pekerja di Kota Surabaya. Metode yang digunakan dalam kegiatan ini adalah penyuluhan dan diskusi online yang bekerja sama dengan Dinas Tenaga Kerja Kota Surabaya dan media Radio RRI. Kegiatan penyuluhan dilakukan oleh Dosen Fakultas Masyarakat kepada masyarakat pekerja. Materi yang disampaikan adalah hazard identification, risk assessment and determining control (HIRADC) terkait optimalisasi penerapan protokol kesehatan, terutama tentang pengendalian COVID-19 yang dapat diterapkan pekerja di tempat kerja. Kemudian dilakukan diskusi online yang juga dipimpin oleh Dosen Fakultas Kesehatan Masyarakat yang membahas pertanyaan serta kendala terkait penerapan protokol kesehatan di tempat kerja.